Between the Possibility to “Teach” Arts and the Imperative Need to Acknowledge the New Young Cultures that Inhabit Today Schools - Charréu, Leonardo (2011)
Far from seeking to scrutinize and Know in technical detail the main methodologies used by art teachers in different historical moments, this paper seeks to highlight and characterize the philosophies that underlie the practice and the consequential reference models. This presupposes that there are more appropriate models than others to face challenges that also changed historically, as well as change young people changed in their psycho-sociological types, for whom planned arts education is offered by our public schools. Teaching according assumptions of another historical time is, therefore, a major misunderstanding of the formal school convinced (like many of their teachers) that it is the people (learners) who will have to adapt to school, to its contents and practices, and not vice versa. This position is often expressed in the phrase “Back in my day… yes school was tougher!“. Supporters, without reservation, to this positioning, which after all is one that is induced by the traditional view of the schooling process, are also those who support the use of pedagogical practices crystallized in time. These practices are absolutely inadequate to the urgent creation of new narratives and competent teaching that could be regenerative in order to tackle the informal learning spaces (television, internet, ipods, video gaming, etc..) that are now in fierce competition with the formal school.